1987
DOI: 10.1111/j.1476-5381.1987.tb11316.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of guinea‐pig tracheal smooth muscle to arachidonate is converted to contraction following epithelium removal

Abstract: The effect of epithelium removal on responses of guinea‐pig isolated trachealis to sodium arachidonate has been examined. Arachidonate (100 μm) caused relaxation of epithelium‐intact preparations, but following epithelium removal, the response to arachidonate was converted to contraction. In the presence of indomethacin (1 μm), arachidonate caused contraction in intact and denuded trachea. Arachidonate also produced concentration‐dependent effects, the qualitative nature of which varied with the presence or ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…We observed (this study) that the contraction of rubbed preparations with AA (10pM) was attenuated by treatment of these tissues with indomethacin. Previous investigators (Nijkamp & Folkerts, 1987;Farmer et al, 1987) were unable to prevent the AA contractile effect in rubbed preparations with indomethacin. The discrepancy between these observations and the results presented here may be due to the high concentrations of AA (100pM) used in those initial studies.…”
Section: Discussionmentioning
confidence: 99%
“…We observed (this study) that the contraction of rubbed preparations with AA (10pM) was attenuated by treatment of these tissues with indomethacin. Previous investigators (Nijkamp & Folkerts, 1987;Farmer et al, 1987) were unable to prevent the AA contractile effect in rubbed preparations with indomethacin. The discrepancy between these observations and the results presented here may be due to the high concentrations of AA (100pM) used in those initial studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of the epithelium, the concentration-response curve obtained after adding MCh mucosally was shifted rightward of the EL curve and was characterized by a smaller maximum response ( Figure 5 and Table 2). The lesser reactivity to MCh after IL addition in intact trachea is a reflection of the epithelial diffusion barrier as well as the release of epithelial-derived modulatory factors (Farmer et al, , 1987Fedan et al, 2006;Fedan and Frazer, 1992;Smith et al, 1993).…”
Section: Effects Of Diacetyl and 23-pentanedione Inhalation On Reactmentioning
confidence: 99%
“…Several investigators have reported alterations in relaxation in ASM from animal models of asthma [322][323][324][325]. Unfortunately, most of them dealt with isometric relaxation (relaxation of tension in muscle maintained at a constant length after cessation of stimulation), which provided information relating to stiffening of the airway wall and not to the relevant parameter of airway lumen narrowing [322][323][324]. In vivo measurements of FEV1 and specific Gaw are better in this regard, but suffer from the drawback that multiple confounding variables are operating simultaneously.…”
Section: Possible Abnormal Relaxation Of Asm In Asthmamentioning
confidence: 99%